Early prediction of prostate cancer biochemical recurrence and identification of disease persistence using PSA isoforms and human kallikrein-2 - Do Carmo Silva, Joana; Vesely, Stepan; Luksanova, Hana; Prusa, Richard; Babjuk, Marko (Tumor biology, 2021)
BACKGROUND: The role of isoforms of prostate specific antigen (PSA) and other kallikrein-related markers in early detection of biochemical recurrence (BCR) after radical prostatectomy (RP) is not well known and serum PSA is currently used in preoperative risk nomograms. OBJECTIVE: The aim of this research was to study pre- and early postoperative levels of important PSA isoforms and human kallikrein-2 to determine their ability to predict BCR and identify disease persistence (DP). METHODS: This study included 128 consecutive patients who underwent RP for clinically localized prostate cancer. PSA, fPSA, %fPSA, [-2]proPSA, PHI and hK2 were measured preoperatively, at 1 and 3 months after RP. We determined the ability of these markers to predict BCR and identify DP. RESULTS: The DP and BCR rate were 11.7%and 20.3%respectively and the median follow up was 64 months (range 3-76 months). Preoperatively, the independent predictors of BCR were PSA (p-value 0.029), [-2]proPSA (p-value 0.002) and PHI (p-value 0.0003). Post-RP, PSA was the single marker correlating with BCR, both at one (p-value 0.0047) and 3 months (p-value 0.0004). PSA, fPSA, [-2]proPSA and PHI significantly correlated to DP at 1 and 3 months post-RP (p-value <  0.05), although PSA had the most significant existing correlation (p-value <  0.0001). CONCLUSIONS: [-2]proPSA and PHI are preoperative predictors of BCR and DP that outperform the currently used serum PSA. At the early postoperative period there is no additional benefit of the other markers tested.
Keywords: nomogramy; Postoperative Period; Protein Isoforms; Male; lokální recidiva nádoru; Neoplasm Grading; Prostate; Tissue Kallikreins; Prostatic Neoplasms; Aged; mužské pohlaví; senioři; prostata; lidé středního věku; prostatektomie; protein - isoformy; pooperační období; Neoplasm Recurrence, Local; prostatický specifický antigen; Nomograms; lidé; stupeň nádoru; Humans; Early Detection of Cancer; nádory prostaty; tkáňové kalikreiny; Prostatectomy; Biomarkers, Tumor; nádorové biomarkery; Prostate-Specific Antigen; časná detekce nádoru; Middle Aged